Implementasi Project Based Learning dalam Penggunaan Aplikasi Komputer : Microsoft Word, Microsoft Excel dan Canva - Eka Rizki Meiwinda; Willy Wijayanti; Rahmawaty Hasibuan; Abraham Horisanto; Muhammad Deddy Syafrullah; Nurul Hijri (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
The development of information technology is a challenge, so we are required to be able to adapt to improve our capabilities in the field of technology. The problem in orphanages is the lack of facilities, funds and volunteers to help improve skills. The aim of this service is to help orphanage children gain skills that can be used in the future. The training method used is lecture and direct practice. The children participating in the training welcomed this training activity happily, seen from the response when the training team carried out direct exposure and practice